Teleprotection simulation lab: Understanding the performance of telecommunication aided protection systems under impaired telecommunication network conditions - Yusof H.A.; Musa A.; Ramli A.Q.; Ridwan M.I. (2023)
Protection using telecommunications, such as the current differential protection schemes, are well known for their selectivity, sensitivity and fast operating times. Such advantages make them a desirable choice for the protection of high voltage transmission lines. However, the reliability and security of these protection schemes depends heavily on the performance of the telecommunication network, which itself is subject to various form of impairments. Tenaga Nasional Berhad (TNB), Malaysia's electrical utility company, depends heavily on the use of current differential protection scheme to protect its high voltage transmission lines. Therefore it is very important to understand how these protection schemes behave when the telecommunication network is impaired. Learning by experience, as several tripping incidents have shown, can be very costly and time consuming. By building a teleprotection simulation lab and using it together with a real-time digital simulator for real load and fault conditions, the performance of these protection schemes under an impaired telecommunication network can be examined and studied in much greater detail under a controlled lab environment. This will enhance the learning process and allow proactive measures to be taken before any unwanted incidents occur. 2012 IEEE.